Exploring multi-level motivations towards green design practices : a system dynamics approach - Li, Qing (2022)
Green building construction is essential to meet severe environmental challenges and achieve sustainability, where designers’ practices are crucial to improve the green performance of construction projects. However, multi-level motivations in green design, such as institutional, market, organizational, and individual initiatives, have not been explored in detail. The dynamic interactions of multiple motivations are rarely examined. The present research reports a systematic and dynamic perspective and investigates how multi-level motivations and their interactions act on designers’ green practices. Multi-level motivations towards green design practices are firstly identified through literature analyses and expert interviews. A system dynamics model characterizing the causal structure of a design assessment system is next developed. It involves interrelationships among the organizational, individual, market, and institutional components influencing designers’ green practices. After model validation to ensure credible output, model simulation is conducted to predict behavioral patterns of the model. Monte Carlo simulation is further used to assess the robustness of the model and understand the effects of changes in input parameters on output. The results show that multi-level motivations interact dynamically and have intricate influences on designers’ green practices. The findings indicate the significant role of government policy in encouraging green practices. It is noted that more policy stimuli may not bring more cost-efficient green outcomes. Besides, the development trends of designers’ green practices are relatively consistent with that of green techniques instead of owners’ requirements. This study suggests that the dynamic interactions of multi-level motivations and intricate effects of motivations are crucial for a comprehensive understanding of complex green design practices. Furthermore, a combination of policy considering hybrid effects turns out to be more effective to reinforce green design practices. A 10% synchronous improvement in green policy implementation, organizational strategy, and designers’ ability could enhance designers’ green practices by 40% compared with the base run. The present research contributes to (a) the state of knowledge by offering a systematic and dynamic view to accurately build the dynamic dependent structure of multiple green motivations and enable the thorough assessment of green design and (b) the state of practice by providing guidelines of joint efforts and systems thinking for sustainable development under complex and dynamic conditions.